A yield-macro model for actuarial use in the United Kingdom. (7th May 2014) - Şahin, Şule; Cairns, Andrew J.G.; Kleinow, Torsten; Wilkie, A. David
Abstract: We construct yield curve models for the UK nominal, real and implied inflation spot rates considering the linkage between their term structures and some macroeconomic variables, in particular, realised inflation and real GDP growth. The paper extends the benchmark "yield-only" model proposed by Şahin et al. (2014 ) by exploring the bidirectional relations between the yield curve factors and the macroeconomic variables and proposes a "yield-macro" model. Although a simple autoregressive order one process fits the yield curve factors quite well the insertion of some macroeconomic variables such as realised inflation and real GDP growth improves the models significantly. We also model macroeconomic variables that take the term structures into account and compare the yield-macro model with Wilkie's model both philosophically and empirically.